CULTURAL HERITAGE IN TRANSITION: NATIONALISMS AND INTERPRETATIONS (ЕтноАнтропоЗум/EthnoAnthropoZoom, 2011)
The paper is an independent student essay prepared for the course Anthropology of the Cultural Heritage within the ethnology and anthropology study program at the Institute for Ethnology and Anthropology on the Faculty of Mathematics and Natural Sciences at the Ss Cyril and Methodius University from Skopje. This paper will contemplate the changes made to the center of Skopje as a result of the placement of monuments and the construction of new museum buildings.
Keywords: cultural heritage